Corticosterone shortens foreign egg ejection distance but not latency in American robins (Turdus migratorius) - Turner, Abbigail M.; Sluis, Victoria N.; Ward, Michael P.; Hauber, Mark E. (Physiology & behavior, 2026)
Obligate brood parasitic birds often face the removal of their eggs by rejector hosts; for example, in North America, American robins (Turdus migratorius) are robust egg rejectors of non-mimetic brown-headed cowbird (Molothrus ater) eggs. Recent studies have investigated the role of various hormones during the anti-parasitic egg-rejection process. Corticosterone, a steroid hormone often released in response to environmental stressors, has previously been found to increase the propensity for female American robins to reject non-mimetic model eggs. To better understand how corticosterone affects other behaviors during the egg-ejection behavioral complex (e.g., the distance the egg is taken from the nest, the latency of rejection decision), we combined two previously used techniques for (i) non-invasive corticosterone delivery and (ii) spatio-temporal tracking of rejected model eggs in wild female American robins. All subjects rejected the non-mimetic model eggs from their clutch, and through a repeated-measures design, we found that the same female robin reduced her egg-ejection distance in the corticosterone treatment relative to the control. In turn, we did not find a treatment effect for ejection latency, perhaps because all but one female already rejected the model egg rapidly (within one hour). Future work should examine whether other known endocrine mediators of egg rejection, including prolactin, similarly affect aspects of egg rejection behavior in this and other hosts of obligate avian brood parasites.